PENGARUH PRODUK, HARGA DAN KUALITAS PELAYANAN, TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS UPSTREET PALOPO) - Ayu Anugrah; Adi Muhammad Fatwah M, Rudianto, Nurjannah (CV. ADIBA AISHA AMIRA, 2023)
This study aims to analyze the effect of product price and service quality on purchasing decisions (Case study of Upstreet Palopo). Sampling method by taking The sampling technique in this study using